Assessment of the Condition of Emergency Building and Intensive Care of Meuraxa Hospital Based on Mantenance Cost Analysis - Khairul Amna; Cut Zukhrina Oktaviani; Ammar Fadhil; Aulia Rachman; Muhammad Azhari; Liza Afra (Electronic Journal of Education, Social Economics and Technology, 2025)
Rumah Sakit Umum Daerah (RSUD) Meuraxa in Mibo is a Badan Layanan Umum Daerah (BLUD). Meuraxa Hospital is obliged to provide comfort and safety for patients. As a BLUD, almost all of its operational costs are sourced from the hospital's own revenue. The hospital building has a variety of ages, and the oldest has been operating for more than 17 years. Therefore, the reliability of the building began to decrease, and there were even building components in a damaged state. Even so, the standardization of hospital performance indicators in 2019 requires that hospital facilities and infrastructure are always in 100% condition. This can be realized by building buildings according to standards and carrying out building maintenance periodically/routinely.  Determining the extent of building damage in compliance with norms and regulations is the aim of the investigation (Peraturan Menteri Pekerjaan Umum Nomor: 24/PRT/M/2008). The method used is to conduct a field observation of building damage. The results of observation of the existing condition of emergency and intensive service building infrastructure obtained a building damage intensity of 1.32%. This condition is included in the category of light maintenance, which is ≤ 35% of the cost of building a new one. Damage is predominant to non-structural components.